The Relationship Between Mature Defenses vs. Needs and Values of Prospective Pedagogues - Anna Seredyńska (Nicolaus Copernicus University in Toruń, 2011)
The role of defense mechanisms is to safeguard a person's ego. They help defend him or herself against fear. Every person makes use of an array of more or less mature defenses. Mature defenses facilitate to pursue the profession of pedagogue. This article presents research which explores the relationship between mature defenses, on the one hand, and needs and values of prospective pedagogues, on the other.